Ambush Marketing Landscape in India: Innovative Practice or Parasitic Marketing? - Shivakanth Shetty, A. (Indian Journal of Marketing, 2012)
The global outreach, sheer size of excited audience and the extreme popularity of the global sports events cutting across cultures has always attracted the attention of the corporates to be associated with events like the Olympics, the World Cup and the Commonwealth Games etc. The widening fiscal deficit of the governments and dwindling private donations have necessitated the organizers to look for a partnership with the corporates to finance these mega events across the world. The rush and competition for earning the much coveted sponsorship and telecast rights of the events resulted in competitive bidding, exclusivity and sometimes the disappointment for the corporates who lost the legitimate opportunity to be associated with the events. However, this blatant commercialization of major sporting events introduced a new sort of phenomenon-ambush marketing, where a competitor of the sponsor might come into play illegitimately and create an association with the event as well as divert the audience’s attention to its business. Though, the phenomenon of ambush marketing has been limited to major sports events, but recent evidence emerging from various countries suggests that marketers have been using it as a weapon of choice to ambush the marketing campaigns of their competitors, thus widening the ambush marketing landscape beyond the major sporting events. The recent ambush act of Samsung against the Nokia signals the widening landscape of ambush marketing in India, and provokes the debate on the relevance of ambush marketing on moral, ethical, judicial and legal grounds. Hence, the present paper makes a critical analysis of the origin and evolution of ambush marketing in India and abroad and explores the dilemma of treating it as a case of innovative practice or parasitic marketing. Finally, by analyzing the legal landscape of ambush marketing in India and abroad, it offers suggestions for the marketers to repulse acts of ambush marketing within the perimeters of legislation in India.